Automatic Program Development A Tribute to Robert Paige - Danvy, Olivier; Henglein, Fritz; Mairson, Harry; Pettorossi, Alberto (Springer Netherlands : Imprint: Springer, 2008)
Automatic Program Development is a tribute to Robert Paige (1947-1999), our accomplished and respected colleague, and moreover our good friend, whose untimely passing was a loss to our academic and research community. We have collected the revised, updated versions of the papers published in his honor in the Higher-Order and Symbolic Computation Journal in the years 2003 and 2005. Among them there are two papers by Bob: (i) a retrospective view of his research lines, and (ii) a proposal for future studies in the area of the automatic program derivation. The book also includes some papers by members of the IFIP Working Group 2.1 of which Bob was an active member. All papers are related to some of the research interests of Bob and, in particular, to the transformational development of programs and their algorithmic derivation from formal specifications. Automatic Program Development offers a renewed stimulus for continuing and deepening Bob's research visions. A familiar touch is given to the book by some pictures kindly provided to us by his wife Nieba, the personal recollections of his brother Gary and some of his colleagues and friends.